Adherence to Best Practice Advice for Diagnosis of Pulmonary Embolism. Issue 1 (January 2022) - Prentice, Donna; Wipke-Tevis, Deidre D.
Abstract : Purpose: This study evaluated clinician adherence to the American College of Physicians Best Practice Advice for diagnosis of pulmonary embolism. Design: A prospective, single-center, descriptive design was utilized. Methods: A heterogeneous sample of 111 hemodynamically stable adult inpatients with a computed tomography pulmonary angiogram ordered was consented. Electronic medical records were reviewed for demographic and clinical variables to determine adherence. The 6 individual best practice statements and the overall adherence were evaluated by taking the sum of "yes" answers divided by the sample size. Results: Overall adherence was 0%. Partial adherence was observed with clinician-recorded clinical decisions rules and obtaining d -dimer (3.6% [4/111] and 10.2% [9/88], respectively) of low/intermediate probability scorers. Age adjustment of d -dimer was not recorded. Computed tomography pulmonary angiogram was the first diagnostic test in 89.7% (79/88) in low/intermediate probability patients. Conclusion: In hemodynamically stable, hospitalized adults, adherence to best practice guidelines for diagnosis of pulmonary embolism was minimal. Clinical utility of the guidelines in hospitalized adults needs further evaluation. Systems problems (eg, lack of standardized orders, age-adjusted d -dimer values, information technology support) likely contributed to poor guideline adherence.